Polylactic acid composition capable of being coated at high speed and preparation method of polylactic acid composition
By using chitosan nanoemulsion in polylactic acid, the problem of insufficient antibacterial performance of polylactic acid coating paper is solved, the antibacterial and flame retardant properties are significantly improved, the risk of bacterial reproduction is extended, and the biodegradability and environmental friendliness of the product are improved. sex.
Patent Information
- Application Number
- CN202411657759.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-11-20
AI Technical Summary
The antibacterial properties of polylactic acid coating paper are insufficient, resulting in bacterial reproduction of disposable tableware under suitable temperature and humidity conditions, affecting human health.
Using chitosan nanoemulsion and polylactic acid, the compatibility and stability of chitosan in the nanoemulsion are improved, antibacterial properties are enhanced, and sodium caseinate and hydroxypropylene are used. The use of base-β-cyclodextrin improves the stability and antibacterial effect of nanoemulsions.
It significantly improves the antibacterial and flame retardant properties of polylactic acid, extends the release performance of chitosan, reduces the risk of bacterial reproduction, and improves the biodegradability and environmental friendliness of the product.
Smart Images

Figure DOBH5FMUPXH1J8TFGTHWCEKAZWT2VGS7PQND3N00 
Figure HWMW5FA0CDM19ZJRMMETXDJJKXJAFCPYM83F2H8Q 
Figure J06ZYK3KKK667LCM9VMLHTYRIJGXBSWKOPRLZGT6
Abstract
Description
Technical Field
[0001] The present application relates to the field of polymer synthetic materials, and more specifically, to a polylactic acid composition capable of high-speed lamination and a preparation method thereof. Background Art
[0002] Polylactic acid, also known as polylactide, belongs to the polyester family. Polylactic acid is a polymer obtained by polymerization with lactic acid as the main raw material. The raw material source is sufficient and renewable. It mainly uses corn, cassava, etc. as raw materials. The production process of polylactic acid is pollution-free and the product is biodegradable. After use, it can be completely degraded by microorganisms in nature under specific conditions, and finally generate carbon dioxide and water, realizing circulation in nature. Therefore, it is an ideal green polymer material.
[0003] Laminated paper is a composite material made by coating plastic particles on the surface of paper through a cast film machine. Its main characteristics are oil-proof, waterproof (relatively) and heat-sealed. Currently, laminated paper made of polyethylene is used to make disposable paper cups, paper bowls and other disposable tableware. However, polyethylene is not biodegradable and is not conducive to environmental protection. Polylactic acid coated paper with polylactic acid coating can greatly reduce the burden on natural resources and the environment compared to disposable tableware made of polyethylene coated paper, and is currently favored by consumers.
[0004] At present, disposable tableware is usually exposed to the air when used, and bacteria are easily bred on the surface of disposable tableware. The oligomers produced by the decomposition of polylactic acid are also easily contaminated by various bacteria. Under suitable temperature and humidity conditions, bacteria can easily multiply, thus affecting human health. Summary of the invention
[0005] In order to improve the defect that the antibacterial performance of polylactic acid is still insufficient, the present application provides a polylactic acid composition that can be coated at a high speed and a preparation method thereof.
[0006] In the first aspect, the present application provides a polylactic acid composition capable of high-speed lamination, which adopts the following technical solution: A high-speed laminating polylactic acid composition comprises the following raw materials in parts by mass: 80-100 parts of polylactic acid, 10-20 parts of chitosan nanoemulsion and 0.1-0.3 parts of a compatibilizer, wherein the chitosan nanoemulsion is chitosan embedded in the nanoemulsion.
[0007] Since polylactic acid is a bio-based material derived from renewable resources such as corn starch or sugarcane, it produces lactic acid through microbial fermentation and then forms polylactic acid through polymerization reaction. It has good biodegradability and can be completely degraded by microorganisms in nature under specific conditions after use, ultimately producing carbon dioxide and water, reducing the impact on the environment.
[0008] Chitosan is a natural high molecular polymer with good antibacterial properties, safety, non-toxicity, biodegradability and other advantages, but chitosan is a natural polysaccharide, composed of N-acetylglucosamine and glucosamine units, with cationicity, because it can be protonated under acidic conditions to form positively charged amino groups. Polylactic acid is a synthetic polyester, which is formed by connecting lactic acid units through ester bonds, and is usually neutral, so the compatibility between the two is poor. Since the chitosan nanoemulsion used in this application is to embed chitosan in nanoemulsion, nanoemulsion can disperse chitosan into nano-level examples, these particles have a larger specific surface area and can be more evenly distributed in the polylactic acid matrix, and embedding chitosan in nano solution can improve the stability of chitosan, promote the interaction between chitosan and microorganisms, enhance the solubility and absorbability of chitosan, and improve the release performance of chitosan, so that chitosan can be well compatible in polylactic acid and improve the antibacterial properties of polylactic acid.
[0009] Preferably, the chitosan nanoemulsion comprises the following raw materials: chitosan prepolymer, sodium caseinate solution and hydroxypropyl-β-cyclodextrin solution.
[0010] As a natural protein, sodium caseinate has good biocompatibility and is non-toxic to cells. As an emulsifier, it can help stabilize the nanoemulsion, making the chitosan prepolymer less likely to aggregate and improving its dispersibility. Hydroxypropyl-β-cyclodextrin, as a stabilizer, is beneficial to improving the stability of the nanoemulsion.
[0011] Preferably, the chitosan nanoemulsion comprises the following raw materials in parts by weight: 4.5-5.5 parts of chitosan prepolymer, 45-55 parts of sodium caseinate solution and 45-55 parts of hydroxypropyl-β-cyclodextrin solution.
[0012] Preferably, the preparation method of the chitosan nanoemulsion is as follows: 45-55 parts of sodium caseinate solution and 45-55 parts of hydroxypropyl-β-cyclodextrin solution are mixed, 4.5-5.5 parts of chitosan prepolymer are added dropwise while stirring, and stirred at room temperature for 1-3 hours to obtain a crude chitosan emulsion, the crude chitosan emulsion is placed in a handheld homogenizer, and homogenized for 1-3 minutes at a speed of 17000-19000rpm, and then the emulsion is treated with ultrasound, the ultrasound treatment frequency is 10-30kHz, the time is 7-13min, the mode is on for 1-3s, and off for 1-3s, to obtain a chitosan nanoemulsion.
[0013] Preferably, the chitosan prepolymer comprises the following raw materials: chitosan, dilute acetic acid solution, ammonium polyphosphate, and sodium phytate solution.
[0014] Preferably, the chitosan is 3-7 g, the dilute acetic acid solution is 240-260 ml, the ammonium polyphosphate is 0.1-0.2 g, and the sodium phytate solution is 8-12 g.
[0015] Preferably, the preparation method of the chitosan prepolymer is as follows: 3-7 g of chitosan is weighed and dissolved in a flask containing 240-260 ml of dilute acetic acid solution, stirred at 20-30° C. until the chitosan is fully dissolved, then heated to 50-70° C., 0.5-1 g of ammonium polyphosphate is added and stirred rapidly for 0.5-1.5 h, then 8-12 g of sodium phytate solution is slowly added, and the reaction is continued for 0.5-1.5 h.
[0016] Chitosan can be dissolved in dilute acetic acid to form a chitosan acetic acid solution, which is beneficial to improve the water solubility of chitosan. Ammonium polyphosphate and polymer have high efficient flame retardant function, but the amount added is generally large, and during use, the flame retardant is easy to precipitate and agglomerate, resulting in uneven dispersion. Therefore, the surface of ammonium polyphosphate is coated so that chitosan is coated on the surface of ammonium polyphosphate, which is beneficial to enhance the flame retardant properties of polylactic acid when the chitosan prepolymer reacts with polylactic acid.
[0017] In a second aspect, the present application provides a method for preparing a polylactic acid composition capable of high-speed lamination, using the following technical solution: A method for preparing a polylactic acid composition capable of high-speed lamination comprises the following steps: S1: Put the polylactic acid into a vacuum drying oven at 115°C-125°C and dry it for 7h-9h; S2: Weigh 80-100 parts of polylactic acid, 10-20 parts of chitosan nanoemulsion and 0.1-0.3 parts of compatibilizer and put them into an extruder at 120-170° C. for melt blending and granulation to obtain a polylactic acid composition.
[0018] In summary, this application has the following beneficial effects: 1. Since polylactic acid is a bio-based material derived from renewable resources such as corn starch or sugarcane, it produces lactic acid through microbial fermentation and then forms polylactic acid through polymerization reaction. It has good biodegradability and can be completely degraded by microorganisms in nature under specific conditions after use, eventually generating carbon dioxide and water, reducing the impact on the environment.
[0019] Chitosan is a natural high molecular polymer with good antibacterial properties, safety, non-toxicity, biodegradability and other advantages, but chitosan is a natural polysaccharide, composed of N-acetylglucosamine and glucosamine units, with cationicity, because it can be protonated under acidic conditions to form positively charged amino groups. Polylactic acid is a synthetic polyester, which is formed by connecting lactic acid units through ester bonds, and is usually neutral, so the compatibility between the two is poor. Since the chitosan nanoemulsion used in this application is to embed chitosan in nanoemulsion, nanoemulsion can disperse chitosan into nano-level examples, these particles have a larger specific surface area and can be more evenly distributed in the polylactic acid matrix, and embedding chitosan in nano solution can improve the stability of chitosan, promote the interaction between chitosan and microorganisms, enhance the solubility and absorbability of chitosan, and improve the release performance of chitosan, so that chitosan can be well compatible in polylactic acid and improve the antibacterial properties of polylactic acid.
[0020] 2. As a natural protein, sodium caseinate has good biocompatibility and is beneficial to cells. It is non-toxic and, as an emulsifier, can help stabilize the nanoemulsion, making the chitosan prepolymer less likely to aggregate and improving its dispersibility. Hydroxypropyl-β-cyclodextrin, as a stabilizer, is beneficial to improving the stability of the nanoemulsion.
[0021] 3. Chitosan can be dissolved in dilute acetic acid to form chitosan acetic acid solution, which is beneficial to improve the water solubility of chitosan. Ammonium polyphosphate and polymer have high flame retardant function, but the amount added is generally large, and during use, the flame retardant is easy to precipitate and agglomerate, resulting in uneven dispersion. Therefore, the surface of ammonium polyphosphate is coated so that chitosan is coated on the surface of ammonium polyphosphate, which is beneficial to enhance the flame retardant properties of polylactic acid when the chitosan prepolymer reacts with polylactic acid. DETAILED DESCRIPTION
[0022] The present application is further described in detail below in conjunction with Examples 1-8 and Comparative Examples 1-2.
[0023] raw material Polylactic acid Shanghai Yuanye Biotechnology Co., Ltd.; chitosan CAS: 9012-76-4; compatibilizer ADR4370S BASF Germany; sodium caseinate CAS: 9005-46-3; hydroxypropyl-β-cyclodextrin Shanghai Aladdin Biochemical Technology Co., Ltd.; acetic acid CAS: 64-19-7; ammonium polyphosphate Jinan Fuming Chemical Co., Ltd.; sodium phytate Hefei BASF Biotechnology Co., Ltd.
[0024] Example Example 1 A polylactic acid composition capable of high-speed lamination comprises the following raw materials: 90g of polylactic acid, 15g of chitosan nanoemulsion, and 0.2g of compatibilizer ADR4370S.
[0025] Specifically, the method for preparing a polylactic acid composition capable of high-speed lamination comprises the following steps: S1: Weigh 5g chitosan and dissolve it in a flask containing 250ml 1% dilute acetic acid solution (the ratio of acetic acid to deionized water is 1:99), stir at 25℃ until the chitosan is fully dissolved, then heat to 60℃, add 0.75g ammonium polyphosphate and stir rapidly for 1h, then slowly add 10g 10% sodium phytate solution (the ratio of sodium phytate to deionized water is 1:9), and continue to react for 1h to obtain chitosan prepolymer; S2: 50 g of 2% sodium caseinate solution (the ratio of sodium caseinate to deionized water is 1:98) and 50 g of 1% hydroxypropyl-β-cyclodextrin solution (the ratio of hydroxypropyl-β-cyclodextrin to deionized water is 1:99) were mixed in a ratio of 1:1, and 5 g of chitosan prepolymer was added dropwise while stirring to a final concentration of 5%, and stirred at room temperature for 2 h to obtain a crude chitosan emulsion. The crude chitosan emulsion was placed in a handheld homogenizer and homogenized at a speed of 18000 rpm for 2 min, and then the emulsion was treated with ultrasound at a frequency of 20 kHz, a time of 10 min, and a mode of on for 2 s and off for 2 s to obtain a chitosan nanoemulsion; S3: Put the polylactic acid into a 120 vacuum drying oven and dry it for 8 hours; S4: 90 g of the dried polylactic acid, 15 g of chitosan nanoemulsion and 0.2 g of compatibilizer ADR4370S were weighed and put into an extruder at 150° C. for melt blending and granulation to obtain a polylactic acid composition.
[0026] Example 2-3 The difference from Example 1 is that the addition amounts of the components of the polylactic acid composition capable of high-speed lamination are different, as shown in Table 1.
[0027] Table 1 The amount of each component added to the polylactic acid composition capable of high-speed lamination in Examples 1-3 (g) Example 4 The difference from Example 1 is that the components of the polylactic acid composition capable of high-speed lamination are different, as shown in Table 2.
[0028] Table 2 The amount of each component added in the polylactic acid composition capable of high-speed lamination in Example 4 (g) Embodiment 5-6 The difference from Example 1 is that the addition amount of each component in the chitosan nanoemulsion is different, as shown in Table 3.
[0029] Table 3 Addition amount of each component in the chitosan nanoemulsion in Example 1 and Examples 5-6 (g) Embodiment 7-8 The difference from Example 1 is that the addition amount of each component in the chitosan prepolymer is different, as shown in Table 4.
[0030] Table 4 Addition amount of each component in chitosan prepolymer in Example 1 and Examples 7-8 (g) Comparative Example Comparative Example 1 The difference from Example 1 is that no chitosan nanoemulsion is added.
[0031] Comparative Example 2 The difference from Example 1 is that the chitosan prepolymer is replaced by an equal amount of chitosan.
[0032] Performance testing Detection Methods 1. Antibacterial performance test Three samples were taken from Examples 1-8 and Comparative Examples 1-2, respectively, and the antibacterial performance was tested according to the standard QB / T 2591-2003 "Test Method and Antibacterial Effect of Antibacterial Plastics", and then the antibacterial rate was obtained and the average value was taken.
[0033] The test data are shown in Table 5.
[0034] Table 5 Antibacterial performance test table of Examples 1-8 and Comparative Examples 1-2 2. Flame retardant performance test Three samples were taken from Examples 1-8 and Comparative Examples 1-2, respectively, and the flame retardant properties of the samples were measured using the UL94 method. The flame retardant grades increased gradually from HB, V-2, V-1 to V-0: HB: The lowest flame retardant grade in the UL94 standard, requiring that for samples 3-13mm thick, the burning speed is less than 40mm / min, and for samples less than 3mm thick, the burning speed is less than 70mm / min, or it is extinguished before the 100mm mark; V-2: After two 10-second combustion tests on the sample, the flame goes out within 60 seconds, and burning objects may fall off; V-1: After two 10-second combustion tests on the sample, the flame goes out within 60 seconds and no burning material falls off; V-0: After two 10-second combustion tests on the sample, the flame goes out within 30 seconds and no burning material falls off.
[0035] The test data are shown in Table 6.
[0036] Table 6 Flame retardant performance test table of Examples 1-8 and Comparative Examples 1-2 Combining Example 1 and Comparative Example 1 and Tables 5 and 6, it can be seen that, relative to Example 1, the antibacterial rate of Comparative Example 1 against Staphylococcus aureus and the antibacterial rate against Escherichia coli have significantly decreased, which shows that, relative to conventional polylactic acid, the addition of chitosan nanoemulsion can effectively improve the antibacterial rate of the sample against Staphylococcus aureus and Escherichia coli, and the flame retardant property of Example 1 is V-0, and the flame retardant property of Comparative Example 1 is HB, and the flame retardant property of Comparative Example 1 is significantly reduced, which shows that, relative to conventional polylactic acid, the addition of chitosan nanoemulsion can effectively improve the flame retardant property of the sample.
[0037] The reason is that when chitosan is embedded in nanoemulsion, nanoemulsion can disperse chitosan into nano-scale particles. These particles have a larger specific surface area and can be more evenly distributed in the polylactic acid matrix. Embedding chitosan in nano solution can improve the stability of chitosan, promote the interaction between chitosan and microorganisms, enhance the solubility and absorbability of chitosan, and improve the release performance of chitosan, so that chitosan can be well compatible with polylactic acid and improve the antibacterial properties of polylactic acid. At the same time, chitosan nanoemulsion contains ammonium polyphosphate, which has a high-efficiency flame retardant function when combined with polymers, but is generally added in large amounts, and during use, the flame retardant is easy to precipitate and agglomerate, resulting in uneven dispersion. Therefore, the surface of ammonium polyphosphate is coated so that chitosan is coated on the surface of ammonium polyphosphate, which is beneficial to enhancing the flame retardant properties of polylactic acid when the chitosan prepolymer reacts with polylactic acid.
[0038] Combining Example 1 and Comparative Example 2 and Tables 5 and 6, it can be seen that, relative to Example 1, the antibacterial rate of Comparative Example 2 against Staphylococcus aureus and the antibacterial rate against Escherichia coli have decreased slightly, which indicates that replacing the chitosan prepolymer with chitosan affects the antibacterial properties of the sample to a certain extent. At the same time, the flame retardant property of Example 1 is V-0, and the flame retardant property of Comparative Example 2 is HB, and the flame retardant property of Comparative Example 2 is significantly reduced, which indicates that, relative to the addition of chitosan, the addition of chitosan prepolymer can effectively improve the flame retardant properties of polylactic acid.
[0039] Combining Example 1 and Examples 2-3 and Tables 5 and 6, it can be seen that, relative to Example 1, the antibacterial rates of Staphylococcus aureus and Escherichia coli in Examples 2 and 3 are slightly decreased, which shows that the amount of each component added in the polylactic acid composition that can be coated at a high speed affects the antibacterial properties of the sample to a certain extent. At the same time, compared with the flame retardant performance of V-0 in Example 1, the flame retardant performance of Examples 2 and 3 is also V-0, which shows that the amount of each component added in the polylactic acid composition that can be coated at a high speed has little effect on the flame retardant properties of the sample.
[0040] Combining Example 1 and Example 4 and Table 5 and Table 6, it can be seen that, relative to Example 1, the antibacterial rate of Example 4 against Staphylococcus aureus and the antibacterial rate against Escherichia coli are reduced, which shows that, relative to the direct addition of chitosan, the addition of chitosan nanoemulsion can effectively improve the antibacterial properties of the sample. At the same time, relative to the flame retardant property of V-0 in Example 1, the flame retardant property of Example 4 is HB, which shows that, relative to the direct addition of chitosan, the addition of chitosan nanoemulsion can effectively improve the flame retardant properties of the sample.
[0041] The reason is that chitosan is a natural high molecular polymer with good antibacterial properties, safety, non-toxicity, biodegradability and other advantages. However, chitosan is a natural polysaccharide composed of N-acetylglucosamine and glucosamine units, which is cationic because it can be protonated under acidic conditions to form positively charged amino groups. Polylactic acid is a synthetic polyester composed of lactic acid units connected by ester bonds, which is usually neutral, so the compatibility between the two is poor.
[0042] Combining Example 1 and Examples 5-6 and Table 5 and Table 6, it can be seen that, relative to Example 1, the antibacterial rates of Staphylococcus aureus and Escherichia coli in Examples 5 and 6 are slightly decreased, which shows that the addition amount of each component in the chitosan nanoemulsion affects the antibacterial properties of the sample to a certain extent. At the same time, relative to the flame retardant performance of V-0 in Example 1, the flame retardant performance of Examples 5 and 6 is also V-0, which shows that the addition amount of each component in the chitosan nanoemulsion has little effect on the flame retardant performance of the sample.
[0043] Combining Example 1 and Examples 7-8 and Tables 5 and 6, it can be seen that, relative to Example 1, the antibacterial rates of Example 7 and Example 8 against Staphylococcus aureus and against Escherichia coli both decreased slightly, which indicates that the amount of each component added in the chitosan prepolymer affects the antibacterial properties of the sample to a certain extent. At the same time, relative to the flame retardant performance of V-0 in Example 1, the flame retardant performance of Examples 7 and 8 is V-1, which indicates that the amount of each component added in the chitosan prepolymer has a certain influence on the flame retardant performance of the sample, and the amount of each component added in the chitosan prepolymer in Example 1 can effectively improve the flame retardant performance of the sample.
[0044] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A polylactic acid composition capable of high-speed lamination, characterized in that: The invention comprises the following raw materials in parts by weight: 80-100 parts of polylactic acid, 10-20 parts of chitosan nanoemulsion and 0.1-0.3 parts of a compatibilizer, wherein the chitosan nanoemulsion is chitosan embedded in the nanoemulsion.
2. A polylactic acid composition capable of high-speed lamination according to claim 1, characterized in that: The chitosan nanoemulsion comprises the following raw materials: chitosan prepolymer, sodium caseinate solution and hydroxypropyl-β-cyclodextrin solution.
3. A polylactic acid composition capable of high-speed lamination according to claim 2, characterized in that: The chitosan nanoemulsion comprises the following raw materials in parts by weight: 4.5-5.5 parts of chitosan prepolymer, 45-55 parts of sodium caseinate solution and 45-55 parts of hydroxypropyl-β-cyclodextrin solution.
4. A polylactic acid composition capable of high-speed lamination according to claim 3, characterized in that: The preparation method of the chitosan nanoemulsion comprises the following steps: mixing 45-55 parts of a sodium caseinate solution and 45-55 parts of a hydroxypropyl-β-cyclodextrin solution, adding 4.5-5.5 parts of a chitosan prepolymer dropwise while stirring, stirring at room temperature for 1-3 hours to obtain a crude chitosan emulsion, placing the crude chitosan emulsion in a handheld homogenizer, homogenizing for 1-3 minutes at a rotation speed of 17000-19000 rpm, and then using ultrasound to treat the emulsion, with an ultrasound treatment frequency of 10-30 kHz, a time of 7-13 minutes, a mode on for 1-3 seconds, and an off for 1-3 seconds, to obtain the chitosan nanoemulsion.
5. A polylactic acid composition capable of high-speed lamination according to claim 4, characterized in that: The chitosan prepolymer comprises the following raw materials: chitosan, dilute acetic acid solution, ammonium polyphosphate and sodium phytate solution.
6. A polylactic acid composition capable of high-speed lamination according to claim 5, characterized in that: The chitosan is 3-7g, the dilute acetic acid solution is 240-260ml, the ammonium polyphosphate is 0.1-0.2g, and the sodium phytate solution is 8-12g.
7. A polylactic acid composition capable of high-speed lamination according to claim 6, characterized in that: The preparation method of the chitosan prepolymer comprises the following steps: weighing 3-7g chitosan and dissolving it in a flask containing 240-260ml dilute acetic acid solution, stirring at 20-30°C until the chitosan is fully dissolved, heating to 50-70°C, adding 0.5-1g ammonium polyphosphate and stirring rapidly for 0.5-1.5h, then slowly adding 8-12g sodium phytate solution and continuing the reaction for 0.5-1.5h.
8. The method for preparing a high-speed laminating polylactic acid composition according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1: Put the polylactic acid into a vacuum drying oven at 115°C-125°C and dry it for 7h-9h; S2: Weigh 80-100 parts of polylactic acid, 10-20 parts of chitosan nanoemulsion and 0.1-0.3 parts of compatibilizer and put them into an extruder at 120-170° C. for melt blending and granulation to obtain a polylactic acid composition.
Citation Information
Patent Citations
Biodegradable PE-coated paper material and preparation method thereof
CN102558797A
New polylactic material used for paper coating
CN102952382A
Novel polylactic acid material and processing technique thereof
CN104371289A
Antibacterial packaging film material and preparation method thereof
CN106479196A
Environment-friendly composite coated paper and preparation method thereof
CN116100909A